2007
DOI: 10.1080/09537100600800743
|View full text |Cite
|
Sign up to set email alerts
|

Platelets possess functional TGF-β receptors and Smad2 protein

Abstract: TGF-beta1 plays a main role in tissue repair by regulating extracellular matrix production and tissue granulation. Platelets are one of the main sources of this cytokine in the circulation. The aim of this study was to evaluate the presence of the TGF-beta receptors on platelets, the effect of TGF-beta1 on platelet aggregation and the underlying intracellular mechanisms. TGF-beta receptors on platelets were studied by flow cytometry and their mRNA by PCR. Platelet aggregation was assessed by turbidimetric meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The cascade of TGF-β/Smad2 and Snail related to EMT was investigated and similar to what was observed in N-cadherin, this cascade was significantly detected in the presence of the highest PRP concentration, and prominently detected in luminal A cells adhered to the network of fibrin bundles (Figure 4C). This cross-talk between the luminal A epithelial cells and PRP-fibrin bundles showed Smad2 expression in human platelets [37]. It is important to note that luminal A cells changed their adhesion site only when exposed to the 7.5% PRP supplementation, contrary to what was observed in the epithelial cells from luminal B and HER2+ tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The cascade of TGF-β/Smad2 and Snail related to EMT was investigated and similar to what was observed in N-cadherin, this cascade was significantly detected in the presence of the highest PRP concentration, and prominently detected in luminal A cells adhered to the network of fibrin bundles (Figure 4C). This cross-talk between the luminal A epithelial cells and PRP-fibrin bundles showed Smad2 expression in human platelets [37]. It is important to note that luminal A cells changed their adhesion site only when exposed to the 7.5% PRP supplementation, contrary to what was observed in the epithelial cells from luminal B and HER2+ tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The specific contribution of TGF-β to thrombus formation however, is not thoroughly elucidated. TGF-β by itself does not induce platelet aggregation [32,34], but seems to have a slightly activating effect when used in combination with different platelet agonists, such as collagen, U46619, ADP and SFLLRNP [34,35]. As Cuende et al showed that inhibitory anti-GARP antibodies can block the release of active TGF-β on Treg, GARP may also be involved in the gradual release of active TGF-β on platelets and endothelium [11].…”
Section: Discussionmentioning
confidence: 99%
“…Increased sEng levels observed in PE women can impair TGF-β1 signaling in the vasculature by reducing the amount of TGF-β1 available to bind to its cell membrane receptors [7]. Moreover, platelet activation is a common feature in PE and activated platelets are the main sources of TGF-β1 in the circulation [37]. Thus, TGF-β1 secreted by activated platelets could play a compensatory role in preserving endothelial function in PE [23].…”
Section: Discussionmentioning
confidence: 99%